The Shamer's daughter - Kaaberbol, Lene (The Shamer chronicles, 2004)
After her mother, a Shamer, is summoned to Dunark for a mission, 10-year-old Dina is forced to use her own special powers as she is caught up in an adventure of political intrigue and survival.